Role of Interleukin-18 in Modulation of Oral Carcinoma Cell Proliferation (Hindawi Limited, 2006)
Interleukin-18 (IL-18), a proinflammatory cytokine, is produced by oral epithelia and carcinoma cells and implicated in tumor regression. Since its direct biological effect on oral cancer cells is not well defined, in this study, we employed a KB cell line to test IL-18 activity. Recombinant human IL-18 significantly inhibited KB cell proliferation in a dose-dependent fashion (P<.05) without increasing cytotoxicity. Analysis of its mode of action showed that IL-18 induced cell cycle arrest in the S phase; however, it did not trigger apoptotic cell death. Findings in this study indicate that the suppression of KB cell proliferation was attributed to the modulation of cell cycle progression, providing a new role of this cytokine in antitumor mechanisms.